2021
DOI: 10.3390/v13091809
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy for Multi-Drug Resistant Respiratory Tract Infections

Abstract: The emergence of multi-drug resistant (MDR) bacteria is recognised today as one of the greatest challenges to public health. As traditional antimicrobials are becoming ineffective and research into new antibiotics is diminishing, a number of alternative treatments for MDR bacteria have been receiving greater attention. Bacteriophage therapies are being revisited and present a promising opportunity to reduce the burden of bacterial infection in this post-antibiotic era. This review focuses on the current eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 87 publications
(202 reference statements)
0
12
0
1
Order By: Relevance
“…Medical use of bacteriophages is focused on phage therapy, i.e., the use of these viruses to combat bacterial infections ( Kortright et al 2019 ). This approach receives more and more attention due to the appearance of numerous bacterial strains resistant to most or even all antibiotics used in clinical practice ( Górski et al 2020 ; Bhargava et al 2021 ; Fathima and Archer 2021 ; Iszatt et al 2021 ). Apart from the direct use of phages infecting pathogenic bacteria to patients, it is also essential to consider their application to control single- or mixed-species biofilms in therapy and protection of medical devices or food ( Mgomi et al 2021 ; Tian et al 2021 ; Topka-Bielecka et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Medical use of bacteriophages is focused on phage therapy, i.e., the use of these viruses to combat bacterial infections ( Kortright et al 2019 ). This approach receives more and more attention due to the appearance of numerous bacterial strains resistant to most or even all antibiotics used in clinical practice ( Górski et al 2020 ; Bhargava et al 2021 ; Fathima and Archer 2021 ; Iszatt et al 2021 ). Apart from the direct use of phages infecting pathogenic bacteria to patients, it is also essential to consider their application to control single- or mixed-species biofilms in therapy and protection of medical devices or food ( Mgomi et al 2021 ; Tian et al 2021 ; Topka-Bielecka et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phage efficiency and safety have been investigated using various bacterial-infected animal models and by conducting human clinical trials [16]. Moreover, an increasing number of case reports have described successful compassionate-use treatment of multidrug-resistant (MDR) bacterial-infected patients by administration of antibiotics in combination with lytic phages, selected in a personalized manner to lyse the isolated MDR pathogen (see [17,18] and recent reviews [16,19]).…”
Section: Introductionmentioning
confidence: 99%
“… 8 The characterisation of therapeutic phages in terms of their biology and bactericidal activity is mandatory before any preclinical trials because the application of non-characterised lytic bacteriophages may cause undesirable virulence as an adaptive response to bacteriophage infection. 5 , 9 In other words, the development of effective strategies, such as phage growth parameters, host range spectrum, the presence of lytic proteins, formulation of phage cocktail and phage synergistic interaction with antibiotic to enhance phage efficacy, is a key prerequisite for optimal treatment of MDR infections caused by K. pneumoniae . Several studies have reported the advantages and drawbacks of phage cocktails in treating MDR bacteria.…”
Section: Introductionmentioning
confidence: 99%